Actualization Of Educational Parenting Patterns For Orphan Children In Ngerjo Village - Yusron Nur Hadi; Zidni Elma Nafia (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This study was motivated by the lack of literature that discusses educational parenting patterns for orphans, so according to researchers it is necessary to research the appropriate educational parenting patterns to implement, so that orphans can develop according to their nature. The type of research used in this study is mixed research in the form of qualitative research with a descriptive approach and literature review. Data collection techniques include observation & literature sourced from competent sources. The results of this research show that: 1.) The educational conditions for orphans are very secure, this can be seen from the requirement for parents to send their children to elementary school in the morning and Madin in the afternoon, 2.) The education pattern for orphans in Ngerjo Village uses the pattern Democratic parenting, 3.) Supporting factors for the actualization of educational parenting for orphans are a.) Community Social Support b.) High Community Awareness, and inhibiting factors are a.) Lack of human resources b.) impatience of teaching staff in developing the community.